Comparison Study between Clinical and Environmental Isolates of Pseudomonas aeruginosa in terms of Pro-inflammatory Cytokines Production in Mice Lungs - Huda Abbas Mohammed; Lubna Abd Muttalib Alshalah (World Journal of Experimental Biosciences, 2023)
Pseudomonas aeruginosa is one of the most widespread bacteria. It causes infectious diseases and at the same time is found in soil and water. It stimulates the pro-inflammatory immune response. The study aims to compare the role of P. aeruginosa isolated from infected burned wounds and that isolated from fresh water in terms of stimulating the pro-inflammatory response of the respiratory tract. In the current study, P. aeruginosa isolates were isolated from infected burned wound swabs (PAC) and from freshwater (PAE). Laboratory mice were stimulated by giving them intranasal (i.n.) standard inoculum of pathogenic and environmental isolates of P. aeruginosa (PAC and PAE respectively). The levels of interleukin (IL-) 1 and tumor necrosis factor (TNF)-alpha (α) were measured in the homogenized mice lungs. The study demonstrated that both isolates (PAC and PAE) stimulated the respiratory system to secrete pro-inflammatory cytokines (IL-1β and TNF-α). Both isolates significantly (P
Keywords: Clinical isolates, Environmental isolates, Interleukin 1, Pseudomonas aeruginosa, Tumor necrosis factor.